Whartonstigma subgen. nov., a new subgenus of the genus Orthostigma Ratzeburg, 1844 from Australasia (Hymenoptera: Braconidae: Alysiinae) - Peris-Felipo, Francisco Javier; Belokobylskij, Sergey A. (Zootaxa, 2020)
The new subgenus Whartonstigma subgen. nov., with type species Orthostigma gallowagi Wharton 2000, of the genus Orthostigma Ratzeburg, 1844 is described and illustrated. Two new species: Orthostigma (Whartonstigma) longipede sp. nov. and O. (W.) papuae sp. nov. are described from Papua New Guinea. A key to all known species of the subgenus Whartonstigma is provided.